Nanocomposite functionalized membranes based on silica nanoparticles cross-linked to electrospun nanofibrous support for arsenic( v ) adsorption from contaminated underground water - Yohai del Cerro, Lucía (2019)
Nanocomposite functionalized membranes were synthesized using surface functionalized mesoporous silica nanoparticles (MCM-NH2 or MCM-PEI) cross-linked to a modified polyacrylonitrile (mPAN) nanofibrous substrate for the removal of 1 mg L-1 of As(V); a concentration much higher than what has been reported for underground water in Argentina. Adsorption studies were carried out in batch mode at pH 8 with nanoparticles in colloidal form, as well as the nanoparticles supported on the modified PAN membranes (mPAN/MCM-NH2 and mPAN/MCM-PEI). Results indicate a twenty-fold improvement in As(V) adsorption with supported nanoparticles (nanocomposite membranes) as opposed to their colloidal form. The adsorption efficiency could be further enhanced by modifying the nanocomposite membrane surface with Fe3+ (mPAN/MCM-NH2-Fe3+ and mPAN/MCM-PEI-Fe3+) which resulted in more than 95%arsenic being removed within the first 15 minutes and a specific arsenic adsorption capacity of 4.61 mg g-1 and 5.89 mg g-1 for mPAN/MCM-NH2-Fe3+ and mPAN/MCM-PEI-Fe3+ nanocomposite membranes, respectively. The adsorption characteristics were observed to follow a pseudo-first order behavior. The results suggest that the synthesized materials are excellent for quick and efficient reduction of As(V)concentrations below the WHO guidelines and show promise for future applications.